Evaluation standards of phytomass trunk components in pine stands of the Northern Steppe of Ukraine - Lovynska , V. M. (Scientific Progress & Innovations, 2019)
The purpose of the article is to develop the standards for evaluating the trunk components of the aboveground phytomass of pine stands in the Northern Steppe of Ukraine. Methods of research. The method of collecting and processing the research material, developed by Professor P.I. Lakyda, was used in the presented paper. The statistical processing, correlation analysis and the search of regression dependences of phytomass components of the common pine trunk on the taxation indices of the tree stand were made. The research results. The working data mass has been formed concerning the results of field and laboratory researches, which characterizes the components of the trunk phytomass for assessing biotic productivity of artificial pine stands in the Northern Steppe of Ukraine. Correlation analysis of the relation closeness of the main phytomass components of the tree stands with their basic taxational signs was carried out. A direct close relation of the trunk phytomass components in the bark and wood without bark with the average tree diameter and the height of stands has been established. The value of correlation coefficient of the bark phytomass with all taxational indices, except the density, demonstrates the moderate relation. Mathematical models have been developed and obtained to assess ordinary pine stands’ phytomass by the components of the trunk wood, trunk wood in the bark, and bark of the trunk. It has been determined that the increase of all the studied components of the aboveground trunk phytomass occurred together with increasing the average heights and diameters of tree stands. The elements of scientific novelty. Standard and information tables have constructed on the basis of regression models for the zone of the Northern Steppe of Ukraine. Practical significance. The obtained systems of standards enable to evaluate ecological and power resources and calculate the carbon sequestration in artificial pine tree stands of the studied region.